Assessing metacognitive strategies for L2 reading: Insights from tertiary ESL classrooms in Kelantan - Awang, Nur Amalina; Mohd Pauzi, Nooradzlina; Wan Ismail, Wan Saiful 'Azzam; Ghani, Mohd Azizi; Hassanuzin, Salsabilla (Quantum Journal of Social Sciences and Humanities (QJSSH, 2024)
This research examines the use of metacognitive strategies in the context of second-language reading employed by tertiary education learners at a public university in Kelantan, Malaysia. Quantitative methodologies were utilised to investigate the strategies used in the ESL classroom. Metacognitive strategies are vital in enhancing reading comprehension and academic achievement, particularly among learners whose English is not their first language. Primarily, this study seeks to identify prevalent metacognitive strategies used, then evaluate their frequency of use concerning three reading strategies; global, problem-solving, and support, as well as analyse the interrelationship among the aforementioned metacognitive reading strategies. Surveys were administered to a sample of tertiary students in their respective ESL classrooms at a public university in Kelantan, for data collection purposes. Accordingly, descriptive and correlation statistical analyses were employed to assess the data and evaluate the effectiveness of metacognitive strategies in predicting the learners’ success, specifically their reading comprehension. The study reveals that learners most commonly recognise problem-solving strategies, and there is a significant positive correlation among all metacognitive reading strategies. The results elucidate the role of metacognitive strategies in enhancing reading abilities within ESL contexts and henceforth propose recommendations for improving ESL teaching practices as informed by these findings.